Faktor Resiko Penyakit Infeksi Menular Seksual (IMS) - Tuntun, Maria (Jurnal Kesehatan, 2018)
Sexually transmitted infections (STIs) are venereal diseases that can be transmitted by 30 types of pathogens through sexual intercourse. The purpose of this study is to find out the risk factors for STI disease in dr. H Hospital. Abdul Moeloek Lampung Province in 2012 - 2016. Type of descriptive analytic research with a cross-sectional design. Research place in RSUD dr. H. Abdul Moeloek Lampung Province, in November-December 2017. The population in this study were patients with STIs recorded in the medical record book of 2012-2016 as many as 191 people and a sample of 186 people. The results of the study obtained 4 types of STIs caused by bacteria, namely gonorrhea, syphilis, condyloma, and bartolinitis. The age range of STI patients is 12-62 years, and the most in the 12-25 year age group is 93 people (50%). The most STI sufferers are men, 100 people (53.8%), with the highest education is high school, which is 121 people (65.1%), more STI patients who work are 102 people (54.8%), and STI sufferers who more from Bandar Lampung, 103 people (55.4%). Risk factors associated with the type of STI are gender (p-value=0.012) and work (p-value=0.012), while age (p-value=0.718), education (p-value=0.368), and residence address (p-value=0.088) there is no relationship with the type of STI.